Educational mobile game application - Liw, Xin Ci (Nanyang Technological University, 2023)
This project aims to address the increased reliance on technology and the importance of math education in children's development during the COVID-19 pandemic. It involves integrating a 2D adventure game with math challenges, targeting primary school children to enhance their problem-solving and critical thinking skills. The report explores pedagogies for game-based learning, utilizing frameworks and theories to design engaging educational components. It outlines the game's development process and showcases different scenes within it.